Factores sociales que impulsan el involucramiento y la participación de las mujeres socias del programa vaso de leche " santísima cruz de motupe" distrito el porvenir - trujillo en el año 2013. - Ramos Sanchez, Jhohany Rosalyn (2013)
This investigation descriptive research, which aims to Know, describe and analyze the social factors that generate the involvement of women members in the management of the glass of milk " Mary help of Christians"in the city of Chepén {En el use de la methodology se utilize herramientas cuantitativas y cualitativas para comprender la relation de variables as mismo It surveyed 42 women members, who had the following inclusion criteria: women members actively participate and efforts involved in cup Milk Program The results show that women members have two major social factors are the confidence generated by the daily interaction with their neighbors and the new knowledge they gained from being part of an organization where management is a primary task and idealized.